DPD of diffusion-weighted MRI. (30th August 2018) - Azhar, M.; Shakil, S.; Greiner, A.; Kauzlarić, D.; Korvink, J.G.
Highlights: Diffusion weighted MRI images are simulated by coupling Bloch equations with flow hydrodynamics. Different diffusion regimes of interest for MRI are successfully imaged. Novel means of evaluating pulse sequence is found to detect different motion in different geometries. Abstract: Diffusion weighted magnetic resonance imaging (DW-MRI) experiments can be simulated by coupling dissipative particle dynamics (DPD) with Bloch equations. DPD gives hydrodynamics with thermal fluctuations at a well-defined temperature by introducing momentum conserving particle interaction forces and a fluctuation dissipation theorem. The Bloch equations are a set of differential equations that describe the evolution of nuclear magnetization as a function of time. Here we successfully simulate DW-MRI by using the solution of Bloch equations for each DPD particle while computing its trajectories through DPD forces. To this end, a spin echo sequence combined with different diffusion-weighting gradients was implemented and tested for the diffusion of a fluid bound by different diffusion regimes. Fluid confinement was easily incorporated, which enabled investigating different diffusion regimes and the performance of different pulse sequences. The three different sequences applied were: spin echo single-sided bipolar gradient, spin echo two-sided bipolar gradient and spin echo uni-polar gradient; and the three imaged diffusion regimes of interest were: free diffusion, localization and motional narrowing.